The martial name in the Zimbabwean conflict (1966–1979) - Pfukwa, Charles (Routledge, 2021)
This article examines the war names used by the guerrillas in the Zimbabwean civil war (1966–1979). It is based on a larger sociolinguistic study dealing with the onomastic and pragmatic significance of these names. The war name was embedded in the history of resistance. Each name can be seen as a text with a long story about a war. The identity of the fighter was part of a wider social discourse that questioned the status quo and explored new political, social and cultural identities. This article focuses on the subcategory of martial names and examines the way in which these names were used to conceal the identity of the bearer and to create a new identity. Renaming became a process of repossession of political and cultural space, an aggressive engagement with the enemy.